EFEKTIVITAS PELAYANAN KARTU TANDA PENDUDUK (KTP) MELALUI INOVASI KLAMPID NEW GENERATION (KNG) DI KELURAHAN NGAGEL KOTA SURABAYA - Saputri, Eka; Tukiman, Tukiman (Jurnal Progress Administrasi Publik, 2024)
As the executor in the formal organizational structure of a country, the bureaucracy is responsible for carrying out the mission and objectives of public services that are oriented toward public satisfaction. Referring to Law Number 25 of 2009, public service is an obligation that the state must provide to the community in order to fulfill all the needs and rights of the people in the field of public services without discrimination. One of the public services provided by the government to the public is services related to population administration. One of the documents related to population administration that is the main focus of this research is the Identity Card (KTP). In the continuously evolving digital era, innovation has become one of the keys to improving public services to the community, including those related to population administration. Therefore, the Surabaya City Government launched the Klampid New Generation (KNG) innovation to simplify the process of population administration services. The aim of this research is to determine the effectiveness of KTP services through the KNG innovation in Ngagel Sub-district, Surabaya City. This research uses a qualitative research method with a descriptive approach. The theory used in this research is James L. Gibson's effectiveness theory, which has five indicators for measuring effectiveness. The findings of this research show that the effectiveness of KTP services through the KNG innovation in Ngagel Sub-district, Surabaya City is proceeding well, in accordance with the effectiveness indicators by James L. Gibson.   Keywords: Effectiveness; Administration; Klampid New Generation (KNG)